Short-term custodial design is outdated: developing knowledge and initiatives for future research and a specialised strategic architecture for police custodial facilities. - Jonescu, Emil (Curtin University, 2013)
This research explores the evolution of WA Police custodial facilities, which uniquely, temporary detain unsentenced people. Adaptation of incompatible spatial strategies have led to a police custodial typology that reflect outdated prison philosophies and design intended for sentenced prisoners. This research developed robust architectural theories derived through critical interdisciplinary investigation developing an understanding of the specialised spatial relationships and operational requirements of police custodial spaces that serve the needs of the custodian and those held.